Diseño de una guía digital de post producción fotográfica para el correcto uso del laboratorio multimedia de la carrera de diseño gráfico computarizado de la Universidad Técnica de Cotopaxi periodo 2013 - Chariguaman Hidalgo, Sara Macrina (2015)
This research was conducted in the province of Cotopaxi, city of Latacunga, San Felipe neighborhood, Simón Rodríguez avenue at the Technical University of Cotopaxi, Engineering Career in Computarized Graphics Design to the students from fourth to eighth cycle, in which the various shortcomings were observed within the field of study, lack of information that exists in the same on the issue of Post Photographic Production. Within the research took into account the observations made available students‟ opinions of subject, which have analyzed objectively, it allowed us to have fundamentals and real data for this proposal to strengthen student learning. Therefore the development of the research work was performed by obtaining information out of with various literature sources both electronic and textual which support the process of development of information….